Faktor-Faktor Yang Mempengaruhi Kualitas Audit Perusahaan LQ45: (Bursa Efek Indonesia Tahun 2020-2022) - Mellinia, Salma Putri; Su'Daa, Saniyya Nabila; Hasanah, Uswatun (Politeknik Negeri Ambon, 2024)
This study examines the factors influencing audit quality, namely firm size, audit rotation, and audit tenure in companies listed in the LQ45 index on the Indonesia Stock Exchange during the period 2020 to 2022. Data were collected from company financial reports and the Indonesia Stock Exchange official website, then analyzed using multiple linear regression. The results indicate that firm size has a positive relationship with audit quality, suggesting that larger companies tend to have better internal controls and risk management. Audit tenure also has a positive relationship with audit quality. Additionally, audit rotation positively influences audit quality, indicating that periodic auditor changes can reduce bias and enhance auditor independence. These findings provide valuable insights for practitioners and regulators in managing relationships with auditors and considering audit rotation policies.